Candida albicans adherence on soft denture liner coated with silica and titanium nanoparticles - Aditama, Pramudya; Maharani, Adella Syvia (Faculty of Dentistry, Universitas Gadjah Mada, 2023)
The soft liner of acrylic resin dentures, used to coat removable partial dentures, still has drawbacks in the easy attachment of Candida albicans fungus. A treatment on the surface of the acrylic resin denture soft liner is needed to reduce the attachment of Candida albicans. Silicon dioxide (SiO2) and titanium dioxide (TiO2) nanoparticles have antimicrobial properties because they can induce photocatalytic production. This study aims to determine the effect of silica and titanium coating concentration on the attachment of Candida albicans to the soft liner of an acrylic resin denture. This study used 48 samples for 2 types of research. Each research consisted of 4 groups with 6 samples each. The samples were disc-shaped, with a diameter of 10 mm and a thickness of 2 mm. Silica and titanium coating materials of 0.5%, 1%, and 2% were obtained by mixing each nanoparticles of 0.5 g, 1 g, and 2 g in 100 ml of ethanol. After the application of the coating, the attachment test of Candida albicans was carried out. Candida albicans in SDA media were counted using a colony counter. The analysis was carried out using a one-way ANOVA test for each experiment. The ANOVA results showed an effect of silica and titanium coating concentrations on the attachment of Candida albicans to the soft liner of an acrylic resin denture (F = 10.929; p < 0.05 for silica, and F = 9.830; p < 0.05 for titanium). The group with a 2% silica coating concentration had the least amount of Candida albicans among all groups (0.48 ± 0.98 x 107 CFU/ml), as well as the group with a 2% titanium coating concentration (0.30 ± 0.83 x 107 CFU/ml). In conclusion, this study shows that the concentration of silica and the 2% titanium coating is the most effective in preventing the attachment of Candida albicans to the soft liner of acrylic resin dentures.